Analysis of Common Problems and Improvement Measures of Pressure Pipeline Inspection - Ding, Ziyue; Jia, Lingyao; Tian, Linxi; Li, Xiangxiang (Journal of Theory and Practice of Engineering Science, 2023)
The recent pressure pipeline reform and China's opening to the outside world have become catalysts for further economic and social development. The oil fields in the northeast and the pure water projects in the southwest have benefited the residents, however, due to the working pressure problems in the pipeline transportation, which are caused by the corrosion of the pipeline materials and the various problems arising from the operation of the pipeline, resulting in long-term safety problems. Therefore, the importance of checking pipeline pressure cannot be missed. In order to ensure the safety of China's natural gas pipelines under pressure, we need to concentrate on analyzing various existing problems and quickly find solutions.